Losses of Brazilian bees: an overview of factors that may affect these pollinators - Carvalho, Stephan [UNESP]; Roat, Thaisa [UNESP]; Pereira, Andrigo M. [UNESP]; Silva-Zacarin, Elaine; Nocelli, Roberta C. F.; Carvalho, Cesar; Malaspina, Osmar [UNESP]; Oomen, P. A.; Thompson, H. (Julius Kuhn-inst, 2012)
The Neotropical region to which Brazil belongs, has a great and rich diversity of natives bees, up to a total of 3.000 species including the allochtone genus Apis that by natural crossing among European and African races produced a hybrid called Africanized honeybee. In this way, beekeeping enjoys a spectacular moment with good production mainly of honey and propolis from Apis mellifera, causing Brazil to be recognized around the world as a country with great potential. Brazilian bee losses nevertheless remain a question, compared with countries of the northern hemisphere where several reports show that the vanishing of honeybees is associated with diseases caused by Varroa, Nosema, virus or pesticides. We can suggest different issues in the Brazilian situation that are directly influencing the honeybee population. Given the extension of the territory and rich flora, all possible food resources and nest sites for the good development of bees may be considered present. However, we verified that annual bee losses in the Southeast can reach 20-30%, mainly due the genetic mechanisms of swarming (nest abandon). Many times the major factor leading to nest abandon is lack of food, often taken mistakenly by the untrained beekeeper as death of the hive caused by diseases or pesticides. Although in Brazil diseases do not represent an important problem for Africanized honeybees, some cases of presence of Nosema ceranae and Varroa destructor led the specialists to precaution and monitoring the colonies. In spite of this, the Brazilian beekeeping is managed without use of any acaricide or antibiotic, producing contaminant-free products. As to pesticides, Brazil has a particular climatic and soil condition that might differently affect the risk of exposure of bees to xenobiotics. For example, comparing the dynamics of carbamate pesticides in soil between Brazil and Europe, it was found that in our condition ten-fold more time is needed to obtain the metabolites sulfone and sulfoxide, both more soluble and toxic than it precursor. Comparing the pesticides consumption, currently Brazil has become the world leader followed by USA, with a total spending of 44.9% herbicide, 28.5% insecticide and 22.1% fungicide. Even with this consumption Brazil still belongs to the group that uses a relatively small amount of active ingredient per hectare, less than Japan and France. However cultures like tomato, potato, citrus, cotton and coffee that are often visited by bees during bloom, are also those where the use of pesticides is needed for the pest control. Thus, little is known yet about pesticide losses of the Brazilian bees! What are real effects of pesticides, toxic plants, diseases, genetic improvement, beekeeping management, starvation or interactions among these? Therefore, our local group on ecotoxicological assessment is trying to increase the knowledge on the pesticides hazard to bees (Apis and non-Apis) in order to protect these.
Keywords: Brazilian bees; overview; pesticide; diseases; environment; protection